Photoactivatable Adhesive Ligands for Light‐Guided Neuronal Growth. (15th May 2018) - Farrukh, Aleeza; Fan, Wenqiang; Zhao, Shifang; Salierno, Marcelo; Paez, Julieta I.; del Campo, Aránzazu
Abstract: Neuro‐regeneration after trauma requires growth and reconnection of neurons to reestablish information flow in particular directions across the damaged tissue. To support this process, biomaterials for nerve tissue regeneration need to provide spatial information to adhesion receptors on the cell membrane and to provide directionality to growing neurites. Here, photoactivatable adhesive peptides based on the CASIKVAVSADR laminin peptidomimetic are presented and applied to spatiotemporal control of neuronal growth to biomaterials in vitro. The introduction of a photoremovable group [6‐nitroveratryl (NVOC), 3‐(4, 5‐dimethoxy‐2‐nitrophenyl)butan‐2‐yl (DMNPB), or 2, 2′‐((3′‐(1‐hydroxypropan‐2‐yl)‐4′‐nitro‐[1, 1′‐biphenyl]‐4‐yl)azanediyl)bis(ethan‐1‐ol) (HANBP)] at the amino terminal group of the K residue temporally inhibited the activity of the peptide. The bioactivity was regained through controlled light exposure. When used in neuronal culture substrates, the peptides allowed light‐based control of the attachment and differentiation of neuronal cells. Site‐selective irradiation activated adhesion and differentiation cues and guided seeded neurons to grow in predefined patterns. This is the first demonstration of ligand‐based light‐controlled interaction between neuronal cells and biomaterials. Abstract : On the light spot : Soft hydrogels functionalized with photoactivatable laminin‐mimetic peptides offer a strategy for optoregulation of the interaction between neuronal cells and a biomaterial. Site‐selective irradiation activated the laminin‐mimetic peptide and provided spatial adhesion and differentiation guidance to seeded neurons.